Functional Characterization of 4′OMT and 7OMT Genes in BIA Biosynthesis - Gurkok, Tugba; Ozhuner, Esma; Parmaksiz, Iskender; Özcan, Sebahattin; Turktas, Mine; İpek, Arif; Demirtas, Ibrahim; Okay, Sezer; Unver, Turgay (Frontiers in Plant Science, 2016)
Alkaloids are diverse group of secondary metabolites generally found in plants. Opium poppy (Papaver somniferum L.), the only commercial source of morphinan alkaloids, has been used as a medicinal plant since ancient times. It produces benzylisoquinoline alkaloids (BIA) including the narcotic analgesic morphine, the muscle relaxant papaverine, and the anti-cancer agent noscapine. Though BIAs play crucial roles in many biological mechanisms their steps in biosynthesis and the responsible genes remain to be revealed. In this study, expressions of 3-hydroxy-N-methylcoclaurine 4′–methyltransferase (4′OMT) and reticuline 7-O-methyltransferase (7OMT) genes were subjected to manipulation to functionally characterize their roles in BIA biosynthesis. Measurements of alkaloid accumulation were performed in leaf, stem, and capsule tissues accordingly. Suppression of 4′OMT expression caused reduction in the total alkaloid content in stem tissue whereas total alkaloid content was significantly induced in the capsule. Silencing of the 7OMT gene also caused repression in total alkaloid content in the stem. On the other hand, over-expression of 4′OMT and 7OMT resulted in higher morphine accumulation in the stem but suppressed amount in the capsule. Moreover, differential expression in several BIA synthesis genes (CNMT, TYDC, 6OMT, SAT, COR, 4′OMT, and 7OMT) were observed upon manipulation of 4′OMT and 7OMT expression. Upon silencing and overexpression applications, tissue specific effects of these genes were identified. Manipulation of 4′OMT and 7OMT genes caused differentiated accumulation of BIAs including morphine and noscapine in capsule and stem tissues.